Evolusi keadaan memaksa (force majeure) dalam kerangka hukum kontrak perjanjian di Indonesia - Masidah, Masidah (Maliki Interdisciplinary Journal, 2024)
The role of contracts holds significant importance in daily life. A contract can be defined as an agreement between parties that creates a legal bond, establishes rights and obligations, and carries consequences if breached. To be deemed valid, a contract must adhere to the provisions outlined in Article 1320 of the Civil Code. Force majeure, referring to a situation in which one party in an agreement cannot fulfill its obligations fully or partially as per the agreement, occurs due to unforeseen events beyond that party’s control at the time of the agreement’s formation. In this scenario, the party unable to meet its obligations cannot be accused or held responsible, and is not obligated to bear the risk. The principle of force majeure is enshrined in Articles 1244 and 1245 of the Civil Code, as well as Articles 1444 and 1445 of the same. Furthermore, this concept is also found in legislation, jurisprudence, court rulings, and is based on expert opinions. The occurrence of force majeure events has implications for agreements and associated risks. The utilization of force majeure requires the presence of good faith from the parties involved. However, in practice, various issues related to force majeure often arise. This research aims to discuss the regulation of force majeure within the context of Indonesia’s legal system, employing a normative juridical methodology. To address these challenges, solutions are needed to ensure the achievement of the primary goal of contract creation: the establishment of fairness for all parties involved.